Determining Priority Strategies to Improve MSME Performance Using AHP Analysis - Annuridya Rosyidta Pratiwi Octasylva; Lilik Noor Yuliati; Hartoyo (School of Business, IPB University (SB-IPB), 2024)
Background: Micro and medium enterprises are the backbone of the economy, contributing more than fifty per cent of the GDP in various countries. However, many SMEs that are difficult to develop cannot even exist in a dynamic business climate. Purpose: Research is necessary to determine priority strategies for improving SMEs performance. Design/methodology/approach: This study used the AHP methodology, with respondents totaling five experts in their fields. The hierarchy in AHP analysis was divided into four levels: Objectives, Factors, Actors, and Alternatives.Findings/results: Based on the results of the analysis, the factors that played a role in the strategy of improving SMEs' performance were the Innovativeness factor, the actor that played the most significant role was SMEs, and the top priority strategy to improve SMEs' performance was to increase the innovative and proactive nature of SMEs through one-on-one mentoring.Conclusion: This comprehensive analysis reveals that fostering growth in SMEs necessitates a multifaceted approach. Cultivating a proactive and inventive mindset through personalized mentoring and encouraging the pursuit of new opportunities are crucial. Furthermore, enhancing adaptability by facilitating exposure to larger business ecosystems through company visits enables SMEs to remain agile and informed. Finally, strengthening digital marketing skills and ensuring product quality are paramount for successful implementation of growth strategies. These findings underscore the importance of a targeted yet diverse approach to empower SMEs, aligning perfectly with the overarching goal of bolstering their performance and ensuring their sustained success.Originality/value (State of the art): While existing literature acknowledges the importance of various factors in SME success, this research provides a novel contribution by: Utilizing AHP: This robust methodology allows for a structured and quantifiable prioritization of factors influencing SME performance, moving beyond descriptive analyses. Expert-Informed Insights: By incorporating the expertise of five field specialists, the study ensures practical relevance and nuanced understanding of the SME landscape. Focus on Proactive Innovation: The findings highlight the crucial role of fostering a proactive and inventive mindset among SME owners as a key driver of performance improvement. Keywords: AHP, MSME performance, SMEs performance, SME’s, priority strategies